Death of adrenocortical cells during murine acute T. cruzi infection is not associated with TNF-R1 signaling but mostly with the type II pathway of Fas-mediated apoptosis - Pérez, Ana Rosa (2017)
Fil: Fil: Perez, Ana Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Rosario. Instituto de Inmunología Clinica y Experimental de Rosario. Universidad Nacional de Rosario. Facultad de Ciencias Médicas. Instituto de Inmunología Clinica y Experimental de Rosario; Argentina